Cooper Test Performance and Total Flight Hours as Predictors of Hypoxia Tolerance Among Indonesian Air Force Pilots - Bimo Wiratomo Baskoro; Nurfanida Librianty; Haneng Marissangan; Prihati Pujowaskito; Andri Welly (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Hypoxia remains one of the most significant physiological threats encountered by military pilots during flight operations, particularly at high altitudes. Reduced oxygen availability can impair cognitive performance, decision-making ability, and operational effectiveness, thereby increasing the risk of aviation incidents. Physical fitness and flight experience are considered important factors that may influence an individual's tolerance to hypoxic exposure. Objective: This study aimed to analyze the relationship between Cooper Test performance and total flight hours with hypoxia tolerance among Indonesian Air Force pilots at dr. Saryanto Institute of Aviation and Aerospace Medicine. Methods: A cross-sectional analytical study was conducted involving 142 Indonesian Air Force pilots who underwent Indoctrination and Aerophysiology Training (ILA) at dr. Saryanto Institute of Aviation and Aerospace Medicine. Secondary data were obtained from medical records, including Cooper Test scores, total flight hours, and hypoxia tolerance measured using Time of Useful Consciousness (TUC). Statistical analyses were performed using Spearman correlation and multivariate regression tests. Results:The mean Cooper Test score was 50.18 ± 7.80, while the mean total flight hours were 1,570.90 ± 1,728.50 hours. The average TUC was 171.27 ± 53.86 seconds. A significant positive correlation was observed between Cooper Test performance and hypoxia tolerance (p < 0.05). Total flight hours demonstrated a significant moderate negative correlation with hypoxia tolerance (p < 0.05). Multivariate analysis showed that total flight hours exerted a greater influence on hypoxia tolerance than Cooper Test performance. Conclusion: Both Cooper Test performance and total flight hours were significantly associated with hypoxia tolerance among Indonesian Air Force pilots. Flight experience demonstrated a stronger predictive value than physical fitness. These findings highlight the importance of maintaining optimal physical fitness and implementing appropriate flight-hour management strategies to improve hypoxia tolerance and aviation safety.